Modern Approach To The Using Of Informations Technologies For Organization Educational Process - Bychkov, O.C.; Chernii, Ю.В. (Journal of Information Technologies in Education (ITE), 2009)
The system of creation of the distance learning course are proposed. with the controlled from distance access for independent preparation; this computer system does not require knowledges of information technologies from teachers.